Does green finance enable firms to promote environmental performance: Evidence from random forest methods? - Xu, Xiaohui; Dong, Ruizhen; Yang, Jun (The Economics and Finance Letters, 2023)
There is a limited body of research that specifically examines the influence of green finance on the environmental performance of enterprises. Employing the panel data of Chinese A-share listed firms from 2012 to 2017 and random forest methods, we intend to examine whether green finance contributes to promoting firms’ environmental performance. If yes, how does green finance promote firms’ environmental performance? Using various empirical tests, we obtain the main results as follows: First, the baseline results show that green finance is conducive to improving firms’ environmental performance. The baseline results are supported in various model settings, including Difference-In-Difference (DID), Bayesian Additive Regression Trees (BART), and matching approaches. Secondly, the internal mechanism tests show that a rise in green innovation and an improvement in green investment efficiency are the main channels through which green finance helps to improve firms’ environmental performance. In addition, considering firm-scale heterogeneity and ownership heterogeneity, we conduct heterogeneity checks. The results of heterogeneity checks show that the positive effect of green finance on the environmental performance of firms is only pronounced for small- and medium-scale firms and for non-state-owned enterprises. Our study expands the framework of green finance research on firms’ environmental performance and provides practical implications for the development of strategies for emerging economies.